2016
DOI: 10.1039/c6cc00711b
|View full text |Cite
|
Sign up to set email alerts
|

Metal-center exchange of tetrahedral cages: single crystal to single crystal and spin-crossover properties

Abstract: An effective single crystal to single crystal transformation from a tetrahedral Ni cage to an FeNi cage was demonstrated. The iron(ii) centers of the FeNi cage can be induced to display spin crossover behaviors with an increasing amount of Fe(II) ions. The SCSC metal-center exchange provides a powerful approach to modify solid magnetic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 41 publications
0
24
0
1
Order By: Relevance
“…With highly ordered cellular-like porous structure, MOFs have been applied in catalalysis, drug delivery, environmental fields, and so on. It has been reported that there are three types of crystal transformation for MOFs, namely, rotation of bond angles, transformation through vapor sorption/desorption, and substitution of metal ions . These transformations caused alterations reflecting in extensiveness like coordination number, space group, color, and magnetism .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With highly ordered cellular-like porous structure, MOFs have been applied in catalalysis, drug delivery, environmental fields, and so on. It has been reported that there are three types of crystal transformation for MOFs, namely, rotation of bond angles, transformation through vapor sorption/desorption, and substitution of metal ions . These transformations caused alterations reflecting in extensiveness like coordination number, space group, color, and magnetism .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there are three types of crystal transformation for MOFs, namely, rotation of bond angles, 8 transformation through vapor sorption/desorption, 9 and substitution of metal ions. 10 These transformations caused alterations reflecting in extensiveness like coordination number, space group, color, and magnetism. 9 Different combinations based on the same metal ions and organic struts brought varied structures and functions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These reversibly formed systems display multiple different mechanisms of ligand exchange, including transimination as well as M–L bond cleavage, which suggests they have potential as stimuli-responsive magnets. However, there are far fewer examples of room temperature, high spin Fe­(II) helicates, and especially the larger cage complexes than their low spin counterparts. Fe-iminopyridyl cages are commonly (if not always) diamagnetic, in contrast to Fe­(II) complexes with other N and O bidentate ligands. , The strong N–Fe–N coordination that allows the formation of highly complex yet stable cage assemblies also favors low spin Fe­(II).…”
Section: Introductionmentioning
confidence: 99%
“…Aus der Literatur ist bekannt, dass der Austausch von Azin‐Bausteinen im letzten Teilschritt der Selbstorganisation durch geeignete Azol‐Bausteine eine effektive Möglichkeit darstellt, die Ligandenfeldstärke zu verringern. Eine solche Verringerung der Ligandenfeldstärke kann letztlich zur Stabilisierung des paramagnetischen high‐spin ‐Zustandes in Eisen(II)‐Kationen führen und bei geschickter Feinabstimmung sogar einen Spin‐Crossover‐Prozess ermöglichen [10d,e, 16, 17a,b, 18, 19] …”
Section: Introductionunclassified